The Great Aten Temple – Selected Interpretative Problems - Jędraszek, Sławomir (Acta Archaeologica Lodziensia, 2021)
The aim of this article is to present an interpretation of the true nature of what was built at the site of the Great Aten Temple at Amarna (Tell el-Amarna), and to show that king Akhenaten had a wider and more varied ideological and cultic vision than he is commonly credited with, in which everyone could appreciate the nature of the god Aten. His religious vision was directed towards intellectual and ideological goals, but also had an economic context. The results of latest archaeological work at the site of Great Temple of Aten (‘House of the Aten’), in the opinion of Professor Barry Kemp suggest the existence of a ‘people’s temple’, which explains much of what the excavations are uncovering.